2006
DOI: 10.1161/01.str.0000217263.55905.89
|View full text |Cite
|
Sign up to set email alerts
|

Not All Patients With Atrial Fibrillation–Associated Ischemic Stroke Can Be Started on Anticoagulant Therapy

Abstract: Background and Purpose-Ischemic stroke patients in atrial fibrillation (AF) have a 10% to 20% risk of recurrent stroke.Warfarin reduces this risk by two thirds. However, warfarin is underutilized in this patient group. We performed a prospective study to determine the reasons why warfarin is not started in these patients. Methods-All patients with AF-associated ischemic stroke over a 12-month period were identified. Demographic and other data, including whether warfarin was commenced or recommended at discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, in a study by Hylek et al, 49% of elderly AF patients (with 2 stroke risk factors) were discharged from the hospital without anticoagulation [11], mainly because of a history of coumadin intolerance and fall risk. Similarly, Somerfield et al, reported that in a group of AF pa- tients admitted with stroke, 30% were not treated with coumadin because of fall risk and only 20% of these patients were on coumadin prior to that despite a known history of AF [12]. These and similar studies suggest that a significant proportion of high-risk AF patients are not considered to be candidates for coumadin therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, in a study by Hylek et al, 49% of elderly AF patients (with 2 stroke risk factors) were discharged from the hospital without anticoagulation [11], mainly because of a history of coumadin intolerance and fall risk. Similarly, Somerfield et al, reported that in a group of AF pa- tients admitted with stroke, 30% were not treated with coumadin because of fall risk and only 20% of these patients were on coumadin prior to that despite a known history of AF [12]. These and similar studies suggest that a significant proportion of high-risk AF patients are not considered to be candidates for coumadin therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Besides, the bleeding risk and the constrains associated with warfarin treatment are concerns in daily practice for many elderly patients: some are unable to comply with the required monitoring and dose adaptation, others fall frequently or have bled. Warfarin appears as underused in most practice surveys, where only a fraction (20 to 65%) of all theoretically eligible patients actually received it [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…From August 2006 to December 2012, we prospectively recruited patients with acute ischemic stroke or TIA admitted to our hospital who met the following 3 criteria: (1) age 18 years or older, (2) had AF based on a 12-lead electrocardiogram obtained at admission, and (3) no rheumatic heart disease or prosthetic heart valve based on the patient's clinical history and echocardiographic examination. According to a predetermined protocol, the clinical data were collected from each patient.…”
mentioning
confidence: 99%
“…Post-stroke severe disability and high risk of falls are common reasons for not using warfarin in patients with ischemic stroke and AF [2]. However, previous studies demonstrated that warfarin reduced post-stroke mortality in patients with AF, and this beneficial effect was independent of age and stroke severity [3,4].…”
mentioning
confidence: 99%